Assessment of the changes in the cellulosic surface of micro and nano banana fibres due to saponin treatment - Cordeiro, Nereida (2021)
The effect of saponin on the surface properties of banana fibres was studied by Inverse Gas Chromatography (IGC). Parameters including the dispersive component of the surface energy, surface heterogeneity, surface area, as well as acid-base surface properties were determined for saponin modified banana micro and nanofibres. These parameters show a more extensive saponin coating on the nanofibres with a network formation which is explained by the higher reactivity of nanofibres due to the higher surface energy, specific interaction and higher surface area presented by the nanofibres. The energetic profile indicates that both micro and nanofibres coated with saponin interact with the same, or similar, energy active sites. Saponin treatment reduces considerably the surface area of the fibres, with the consequent decrease in the monolayer capacity. The interaction with the polar probes clearly indicates that saponin treatment creates new polar active sites for specific interactions in both samples. However, the treatment increases predominately the basicity of the fibre surface with more relevance to the nanofibres. This behaviour will lead to better polymer/fibre interaction during composite preparation.